Respons Pembaca terhadap Tokoh Utama Wanita dalam Novel Layangan Putus Karya Mommy ASF: Kajian Resepsi Sastra - Trianingsih, Arsidah; Hanum, Irma Surayya; Nugroho, Bayu Aji (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
Literary works are created for enjoyment and as a means of authorship. Mommy ASF's novel "Layangan Putus" describes a strange problem in household life experienced by a woman as a wife and mother. The novel was very famous at the beginning of 2022 and has attracted much attention of Indonesian public in particular to the problems experienced by the main woman in the story, named Kinan. The study aims to describe the reader's response to the female protagonist in Mommy ASF's novel "Layangan Putus" through a literary reception study. This research is a kind of field research with a qualitative descriptive approach and using the Sinkrois reception method. The research data is a survey of readers from Eastern Kalimantan, in Samarinda Seberang district, with 20 respondents. The results of the interview were subsequently submitted and a summary withdrawal was made from the literary reception analysis. In this study the object used is the reader's response to the novel through the results of the interview.Based on the results of the research concluded the reaction of most of the respondents to the novel "Layangan Putus" by Mommy ASF assumed that the main character of the woman in the novel is inherent a strong, wise, self-sufficient and patient attachment in the face of the test. In the analysis of the attachment, the main characters of women belong to the round characters who have a good character, firm, religious, but have a soft weak side easy to frail in silence which makes her more likely to mimic complex life. It was revealed to readers as proof that readers succeeded in accepting, appreciating and giving statements of admiration for the main character of the woman in the novel "Layangan Putus" by Mommy ASF.